Prevalence of Vitamin D Deficiency and Insufficiency in Kosovo Population - Baruti-Gafurri, Zana; Kafexholli, Ardita; Dervishi, Bardha; Sylaj, Rilind; Shabani, Krenare; Musliu, Dijon (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Vitamin D deficiency is a global health problem, but it is not known about its status in the Kosovo population. AIM: The purpose of this study is to determine the status of Vitamin D deficiency and insufficiency in our population. MATERIALS AND METHODS: Data collection was done from January 2020 to July 2021, during which period blood samples were collected. The sampling was done for 769 selected subjects and statistical data (frequency, mean values, and standard deviation) have been analyzed for 25-hydroxyvitamin D [25(OH)D] concentration. They were categorized by age group, gender, and level of 25(OH)D. The prevalence and percentage of Vitamin D deficiency and insufficiency in the study population were evaluated. RESULTS: The mean concentration of 25(OH)D in the serum of the study group was 18.3 ng/ml. The mean value was significantly lower for females when compared for that of males (17.89 and 19.58 ng/ml, respectively), with p < 0.0035, but there was no significant difference between age groups. The level of 25(OH)D less than 20 ng/ml was observed in 62% of the cases in our study population with a slight difference between female (63.6%) and male (57.2%) group. The age group of >60 had 25(OH)D deficiency in 62.3% of cases when compared to other age group categories. Vitamin D deficiency was present in 20.2% of cases; meanwhile, its insufficiency was present in 41.9% of cases. Vitamin D deficiency was observed in 21.1% of females and 17.1% of males, while 42.4% of females, respectively, and 40.1% of males had Vitamin D insufficiency. CONCLUSION: The mean values of 25(OH)D in the study population are relatively low, which corresponds to significant Vitamin D deficiency and insufficiency in all age groups, and which may also have serious implications for their overall health.